Training practices and overtraining syndrome in Swedish age-group athletes - Kenttä, G.; Hassmen, P.; Raglin, J. S. (International Journal of Sports Medicine, 2001)
Heavy training in combination with inadequate recovery actions can result in the overtraining/staleness syndrome and burnout. Even young and aspiring elite athletes develop staleness. The aim was therefore to determine the incidence and nature of staleness, and its association with training behavior and psychosocial stressors in young elite athletes. A sample of 272 individuals from 16 sports completed questionnaires on training, staleness, and psychosocial stress and 37% reported being stale at least once. The incidence rate was higher for individual sports (48%) compared with team (30%) and less physically demanding sports (18%). Stale athletes reported greater perceptual changes and negatively elevated mood scores in comparison to healthy athletes. Staleness was distinguished from burnout on the basis of motivational consequences; 41 % of the athletes lost their motivation for training, which in turn indicates a state of burnout. Further, 35 % of the athletes reported low satisfaction with time spent on important relationships, 29% rated the relationship with their coach as ranging from very, very bad to only moderately good. The results indicate that staleness is a widespread problem among young athletes in a variety of sports, and is not solely related to physical training, but also to non-training stressors.